Scratch-resistant coating and preparation method thereof
By forming a complex network structure with modified silicon carbide fibers and acrylic resin, and combining it with nanofiller treatment, a scratch-resistant coating was prepared, which solved the problems of insufficient toughness and dispersibility of traditional coatings and achieved multiple properties such as high hardness, wear resistance and self-cleaning.
Patent Information
- Application Number
- CN202610001559.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-04
- Publication Date
- 2026-02-06
AI Technical Summary
Traditional scratch-resistant coatings, while improving hardness, lack toughness and dispersibility, and are difficult to achieve multiple properties such as scratch resistance, corrosion resistance, and hydrophobicity at the same time, thus failing to meet the needs of modern materials surface engineering.
A complex network structure is formed by modified silicon carbide fiber and acrylic resin, combined with nanofillers and hydrophobic modification treatment to prepare a scratch-resistant coating. This coating enhances wear resistance and self-cleaning ability by improving toughness and adhesion.
It improves the coating's scratch resistance, abrasion resistance, and weather resistance, enhances adhesion and self-cleaning ability, and meets the multiple performance requirements of modern material surface engineering.
Smart Images

Figure CN121471778A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of chemical coating technology, and particularly relates to a scratch-resistant coating and its preparation method. Background Technology
[0002] With the rapid development of modern industry and high-tech products, various materials and products, such as automotive shells and interiors, electronic product shells, optical lenses, furniture surfaces, and high-end packaging materials, inevitably come into contact with, rub against, and collide with hard objects during daily use, transportation, and cleaning, resulting in scratches, abrasions, and wear on the surface. This surface damage not only severely affects the product's aesthetic appearance, reduces the consumer experience and the product's commercial value, but also impairs its functionality. For example, for optical components, surface scratches can cause light scattering, affecting light transmittance and image quality; for automotive clear coat, scratches can accelerate the aging and corrosion of the underlying material.
[0003] Therefore, developing a high-performance scratch-resistant coating that imparts excellent resistance to mechanical damage to the substrate surface without impairing its original optical properties and other physicochemical properties has become a crucial and highly challenging task in the field of materials surface engineering, with huge market demand and broad application prospects.
[0004] Traditional scratch-resistant coating technologies primarily rely on high-crosslinking-density resin systems (such as high-hardness polyurethane acrylates) or the addition of inorganic nanoparticles (such as Al2O3 and ZrO2) to improve surface hardness and scratch resistance. However, these methods generally have significant drawbacks: while increasing hardness, they often sacrifice toughness, leading to increased coating brittleness and making the coating prone to microcracks or even peeling under impact or deformation; furthermore, the introduction of inorganic fillers tends to agglomerate, making it difficult to disperse evenly in the resin matrix, and instead becoming stress concentration points, reducing overall performance. In addition, traditional coatings are usually single-function, making it difficult to simultaneously achieve multiple properties such as scratch resistance, corrosion resistance, and hydrophobicity, and failing to meet the increasingly stringent requirements for environmental adaptability and service life.
[0005] To address the aforementioned problems, this invention aims to provide a novel scratch-resistant coating that, while maintaining high hardness and high wear resistance, significantly improves toughness and adhesion, and further introduces additional functions such as hydrophobicity, self-cleaning, and corrosion resistance to meet the current demands of the consumer market. Summary of the Invention
[0006] To overcome the shortcomings of existing technologies, one of the objectives of this invention is to provide a scratch-resistant coating. The scratch-resistant coating obtained by this invention incorporates novel modified silicon carbide fibers, and polyethylene glycol monomethyl ether acrylate, isodecanyl acrylate, and acrylic acid are polymerized to form an acrylic resin. The modified silicon carbide fibers and acrylic resin intertwine to form a complex network structure, reducing the brittleness of the coating and preventing cracking. It exhibits excellent scratch resistance, not only improving the coating's wear resistance and weather resistance but also enhancing its mechanical properties. Furthermore, the scratch-resistant coating of this invention has strong self-cleaning ability, good adhesion, and good corrosion resistance.
[0007] A second objective of this invention is to provide a method for preparing a scratch-resistant coating. This method is simple and easy to operate.
[0008] One of the objectives of this invention is achieved through the following technical solution: A scratch-resistant coating comprising the following raw materials in parts by weight: 15-20 parts polyethylene glycol monomethyl ether acrylate, 25-30 parts isodecaacrylate, 40-50 parts acrylic acid, 10-15 parts reactive diluent, 4-5 parts photoinitiator, 0.5-1 part leveling agent, 3-7 parts nanofiller, and 8-12 parts modified silicon carbide fiber; The preparation process of the modified silicon carbide fiber is as follows: (1) Add silicon carbide fiber to the solvent, then add the catalyst, stir at room temperature, add tetrabutyl titanate, heat to react, separate the product, and heat the product to obtain pretreated silicon carbide. (2) Add the silicon carbide pretreated in step (1) to the solvent, then add the silane coupling agent, and after the reaction, obtain silicon carbide modified with silane coupling agent; (3) Add the silicon carbide modified by the silane coupling agent in step (1) to the solvent, then add methacrylate monomer and initiator, and after the reaction, obtain modified silicon carbide fiber.
[0009] Further, in step (1), the ratio of silicon carbide fiber, catalyst and tetrabutyl titanate is 1-2g: 1-1.5mL: 0.5-0.9mL; the ratio of silicon carbide fiber and solvent is 1-2g: 50mL; the catalyst is an ammonia solution with a mass concentration of 25%; and the solvent is anhydrous ethanol.
[0010] Further, in step (1), the stirring time at room temperature is 10-15 min; the heating reaction temperature is 40-50℃ and the time is 7-10 h; the heat treatment temperature is 270-280℃ and the time is 1-2 h.
[0011] Further, in step (2), the ratio of the amount of pretreated silicon carbide, silane coupling agent, and solvent is 3g:0.2-0.4g:300-400g; the solvent is prepared by mixing ethanol and water in a volume ratio of 1:1; the silane coupling agent is vinyltrimethoxysilane; and the reaction time is 20-30min.
[0012] Further, in step (3), the ratio of the amount of silicon carbide modified by the silane coupling agent to the solvent is 1g:60-100mL, and the mass ratio of the silicon carbide modified by the silane coupling agent, the methacrylate monomer, and the initiator is 1:(1.5-3):(1-1.5); the solvent is anhydrous ethanol; the methacrylate monomer is trifluoroethyl methacrylate; the initiator is azobisisobutyronitrile; the reaction temperature is 60-70℃, and the time is 40-60min.
[0013] Furthermore, the preparation process of the nanofiller is as follows: nanographene is added to an aqueous solution of chitosan and stirred at room temperature to obtain a dispersion. The dispersion is ball-milled and dried. The dried product is added to water, and then pretreated carboxymethyl cellulose is added. The mixture is heated to react and obtain the nanofiller.
[0014] Further, the preparation process of the pretreated carboxymethyl cellulose is as follows: Carboxymethyl cellulose is added to water, then urea and sodium hydroxide are added, stirred and mixed evenly, and then freeze-dried to obtain pretreated carboxymethyl cellulose; the mass ratio of sodium hydroxide, urea, water and carboxymethyl cellulose is (5-7):(8-12):(98-100):(3-4).
[0015] Further, the mass ratio of the nano-graphene and the chitosan aqueous solution is 1:(5-7); the chitosan aqueous solution is prepared by mixing chitosan and acetic acid aqueous solution at a mass ratio of 1:(9-10), the concentration of the acetic acid aqueous solution is 5-8wt%, the stirring time at room temperature is 1-2h; the ball milling speed is 400-500rpm, and the time is 10-15h; the ratio of the dried product, pretreated carboxymethyl cellulose, and water is 5g:1-1.5g:90-100mL; the heating reaction temperature is 40-50℃, and the time is 3-5h.
[0016] Further, the reactive diluent is any one of 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, or trimethylolpropane triacrylate; the photoinitiator is 1-hydroxycyclohexylphenyl ketone; and the leveling agent is BYK-333.
[0017] The second objective of this invention is achieved by the following technical solution: The method for preparing the scratch-resistant coating of the present invention includes the following steps: S1. Weigh each raw material according to the stated weight parts, mix polyethylene glycol monomethyl ether acrylate, isodecanyl acrylate and acrylic acid evenly, add 30-40% of the mass of photoinitiator, and polymerize to obtain acrylic resin; S2. Add reactive diluent, the remaining photoinitiator, and leveling agent to acrylic resin and stir until homogeneous. Then add nanofiller and stir until homogeneous. Next, add modified silicon carbide fiber and stir until homogeneous to obtain a coating. Apply the coating to the surface of the substrate and cure it under ultraviolet light to obtain a scratch-resistant coating.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. In this invention, silicon carbide fibers are first treated with tetrabutyl titanate to form an amorphous titanium dioxide coating on the fiber surface. After high-temperature firing, the amorphous titanium dioxide transforms into anatase crystals, possessing higher surface energy and more active sites, thus improving its binding ability with silane coupling agents. Then, vinyl groups are introduced by modification with silane coupling agents. Under the action of an initiator, polymer chains are formed on the silicon carbide fiber surface through a polymerization reaction. The modified silicon carbide fibers and the synthesized acrylic resin intertwine to form a complex network structure, reducing the brittleness of the coating and preventing cracking. The modified silicon carbide fibers and all raw material components exhibit good compatibility, which not only helps improve the dispersibility of the silicon carbide fibers and prevent agglomeration, but also enables the coating to effectively resist external scratches, improve its wear resistance and weather resistance, and enhance its mechanical properties. Furthermore, this invention introduces fluorine atoms into the silicon carbide fiber surface, giving the coating good hydrophobicity and self-cleaning ability.
[0019] 2. This invention pretreats carboxymethyl cellulose to increase its specific surface area and provide more active sites. Introduced chitosan forms a stable coating layer on the surface of nano-graphene, which then cross-links with the pretreated carboxymethyl cellulose to prepare a filler. On one hand, this nanofiller exhibits good dispersibility, improving the adhesion between the coating and the substrate. On the other hand, the modified nanofiller contains nano-graphene, which effectively extends the penetration path of water, air, and corrosive ions, improving the coating's water resistance and corrosion resistance. Attached Figure Description
[0020] Figure 1 This is an electron microscope image of the modified silicon carbide fiber obtained in Example 1 of the present invention; Figure 2 This is an electron microscope image of the nanofiller obtained in Example 1 of the present invention. Detailed Implementation
[0021] The present invention will now be further described with reference to the accompanying drawings and specific embodiments. It should be noted that, without conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments. Specific conditions not specified in the embodiments are performed according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, all reagents or instruments used are conventional products obtained through commercial channels.
[0022] The graphene oxide sheets of this invention have a diameter of 5-30 μm and a thickness of 20-200 nm; the silicon carbide fibers have a diameter of 5-20 µm.
[0023] Example 1 A scratch-resistant coating comprising the following raw materials in parts by weight: 18 parts polyethylene glycol monomethyl ether acrylate, 27 parts isodecaacrylate, 45 parts acrylic acid, 12 parts reactive diluent (1,6-hexanediol diacrylate), 4.5 parts photoinitiator (1-hydroxy-cyclohexyl benzophenone), 0.8 parts leveling agent BYK-333, 5 parts nanofiller, and 10 parts modified silicon carbide fiber; The preparation process of the modified silicon carbide fiber is as follows: (1) Mix silicon carbide fiber and anhydrous ethanol in a ratio of 1.5g:50mL; then add ammonia solution with a mass concentration of 25%, stir at room temperature for 13min, and then add tetrabutyl titanate. The ratio of silicon carbide fiber, ammonia solution and tetrabutyl titanate is 1.5g:1.2mL:0.7mL; react at 45℃ for 8h, then centrifuge at 1500rpm to separate the product, wash the product with anhydrous ethanol 5 times, and then treat the product at 275℃ for 1.5h to obtain pretreated silicon carbide. (2) Ethanol and water are mixed in a volume ratio of 1:1 to prepare a mixed solution. The silicon carbide pretreated in step (1) is added to the above mixed solution, and then vinyltrimethoxysilane is added. The ratio of the amount of pretreated silicon carbide, vinyltrimethoxysilane and mixed solution is 3g:0.3g:350g. The reaction is stirred for 25min. The reaction solution is filtered and dried to obtain silicon carbide modified with silane coupling agent. (3) The silane coupling agent-modified silicon carbide obtained in step (1) and anhydrous ethanol were mixed evenly at a ratio of 1 g: 80 mL. Then, trifluoroethyl methacrylate and azobisisobutyronitrile were added. The mass ratio of silane coupling agent-modified silicon carbide, trifluoroethyl methacrylate, and azobisisobutyronitrile was 1:2:1.2. The mixture was reacted at 65 °C for 50 min. After filtration, washing, and drying, modified silicon carbide fibers were obtained. The electron micrograph of the modified silicon carbide fibers is shown below. Figure 1 As shown.
[0024] The preparation process of the nanofiller is as follows: Sodium hydroxide, urea, deionized water and carboxymethyl cellulose are weighed according to the mass ratio of 6:10:99:3.5. Carboxymethyl cellulose is added to deionized water, and then urea and sodium hydroxide are added. After stirring and mixing evenly, the mixture is freeze-dried to obtain pretreated carboxymethyl cellulose. Chitosan was dissolved in a 7% (w / w) aqueous solution of acetic acid at a mass ratio of 1:9.5. The solution was heated to 55°C and stirred until dissolved to obtain an aqueous chitosan solution. Nanographene was added to the chitosan solution at a mass ratio of 1:6, and the mixture was stirred at room temperature for 1.5 h to obtain a dispersion. The dispersion was placed in a grinding bowl and ball-milled continuously at 400 rpm for 10 h for exfoliation. The resulting product was dried under vacuum at 60°C. The dried product was added to deionized water, followed by pretreated carboxymethyl cellulose. The ratio of dried product, pretreated carboxymethyl cellulose, and deionized water was controlled at 5 g:1.2 g:95 mL. The mixture was reacted at 45°C for 4 h, allowed to stand for 12 h, and then centrifuged at 5000 rpm for 30 min. The precipitate was washed with deionized water and dried to obtain the nanofiller. The electron micrograph of the nanofiller is shown below. Figure 2 As shown.
[0025] This embodiment also provides a method for preparing a scratch-resistant coating, comprising the following steps: S1. Weigh each raw material according to the stated weight proportions, mix polyethylene glycol monomethyl ether acrylate, isodecanyl acrylate, and acrylic acid evenly, add 35% of the mass of the photoinitiator, and under nitrogen protection, apply 365nm ultraviolet light (intensity 20mW / cm²). 2 Under these conditions, the polymerization reaction yields acrylic resin; S2. Add reactive diluent, the remaining photoinitiator, and leveling agent to the acrylic resin, stir until homogeneous, then add nanofiller and stir until homogeneous; then add modified silicon carbide fiber and stir until homogeneous to obtain a coating. Apply the coating to the substrate surface and test under a 365nm ultraviolet lamp (intensity 20mW / cm²). 2 After curing, a scratch-resistant coating is obtained.
[0026] Example 2 A scratch-resistant coating comprising the following raw materials in parts by weight: 15 parts polyethylene glycol monomethyl ether acrylate, 25 parts isodecaacrylate, 40 parts acrylic acid, 10 parts reactive diluent (tripropylene glycol diacrylate), 4 parts photoinitiator (1-hydroxy-cyclohexyl benzophenone), 0.5 parts leveling agent BYK-333, 3 parts nanofiller, and 8 parts modified silicon carbide fiber; The preparation process of the modified silicon carbide fiber is as follows: (1) Mix silicon carbide fiber and anhydrous ethanol at a ratio of 1g:50mL; then add ammonia solution with a mass concentration of 25%, stir at room temperature for 10min, and then add tetrabutyl titanate. The ratio of silicon carbide fiber, ammonia solution and tetrabutyl titanate is 1g:1mL:0.5mL; react at 40℃ for 10h, then centrifuge at 1500rpm to separate the product, wash the product with anhydrous ethanol 5 times, and then treat the product at 270℃ for 2h to obtain pretreated silicon carbide. (2) Ethanol and water are mixed in a volume ratio of 1:1 to prepare a mixed solution. The silicon carbide pretreated in step (1) is added to the above mixed solution, and then vinyltrimethoxysilane is added. The ratio of the amount of pretreated silicon carbide, vinyltrimethoxysilane and mixed solution is 3g:0.3g:300g. The reaction is stirred for 20min. The reaction solution is filtered and dried to obtain silicon carbide modified with silane coupling agent. (3) The silicon carbide modified with silane coupling agent obtained in step (1) and anhydrous ethanol are mixed evenly at a ratio of 1g:60-100mL. Then, trifluoroethyl methacrylate and azobisisobutyronitrile are added. The mass ratio of silicon carbide modified with silane coupling agent, trifluoroethyl methacrylate and azobisisobutyronitrile is 1:1.5:1. The mixture is reacted at 60℃ for 60min. Then, it is filtered, washed and dried to obtain modified silicon carbide fiber.
[0027] The preparation process of the nanofiller is as follows: Sodium hydroxide, urea, deionized water, and carboxymethyl cellulose are weighed according to a mass ratio of 5:8:98:3; carboxymethyl cellulose is added to deionized water, followed by urea and sodium hydroxide; after stirring and mixing evenly, the mixture is freeze-dried to obtain pretreated carboxymethyl cellulose; chitosan is dissolved in a 5% acetic acid aqueous solution, with a mass ratio of chitosan to acetic acid aqueous solution of 1:9; the temperature is raised to 55°C, and the mixture is stirred until dissolved to obtain an aqueous solution of chitosan; nano-graphene is added to the chitosan aqueous solution, and the nano-graphene and chitosan aqueous solution... The mass ratio was 1:5, and the mixture was stirred at room temperature for 1 hour to obtain a dispersion. The dispersion was placed in a grinding bowl and continuously ball-milled at 400 rpm / min for 10 hours for exfoliation. The resulting product was dried under vacuum at 60°C. The dried product was added to deionized water, and then pretreated carboxymethyl cellulose was added. The ratio of the dried product, pretreated carboxymethyl cellulose, and deionized water was 5 g: 1 g: 90 mL. The mixture was reacted at 40°C for 5 hours, allowed to stand for 12 hours, and then centrifuged at 5000 rpm for 30 minutes. The precipitate was washed with deionized water and dried to obtain the nanofiller.
[0028] This embodiment also provides a method for preparing a scratch-resistant coating, comprising the following steps: S1. Weigh each raw material according to the stated weight proportions, mix polyethylene glycol monomethyl ether acrylate, isodecanyl acrylate, and acrylic acid evenly, add 30% of the mass of the photoinitiator, and under nitrogen protection, under a 365nm ultraviolet lamp (intensity 20mW / cm²). 2 The polymerization reaction yields acrylic resin; S2. Add reactive diluent, the remaining photoinitiator, and leveling agent to the acrylic resin and stir until homogeneous. Then add nanofiller and stir until homogeneous. Next, add modified silicon carbide fiber and stir until homogeneous to obtain a coating. Apply the coating to the substrate surface and test under a 365nm UV lamp (intensity 20mW / cm²). 2 After curing, a scratch-resistant coating is obtained.
[0029] Example 3 A scratch-resistant coating comprising the following raw materials in parts by weight: 20 parts polyethylene glycol monomethyl ether acrylate, 30 parts isodecaacrylate, 50 parts acrylic acid, 15 parts reactive diluent (trimethylolpropane triacrylate), 5 parts photoinitiator (1-hydroxycyclohexyl benzophenone), 1 part leveling agent BYK-333, 7 parts nanofiller, and 12 parts modified silicon carbide fiber; The preparation process of the modified silicon carbide fiber is as follows: (1) Mix silicon carbide fiber and anhydrous ethanol in a ratio of 2g:50mL; then add ammonia solution with a mass concentration of 25%, stir at room temperature for 15min, and then add tetrabutyl titanate. The ratio of silicon carbide fiber, ammonia solution and tetrabutyl titanate is 2g:1.5mL:0.9mL; react at 50℃ for 7h, then centrifuge at 1500rpm to separate the product, wash the product with anhydrous ethanol 5 times, and then treat the product at 280℃ for 1h to obtain pretreated silicon carbide. (2) Ethanol and water are mixed in a volume ratio of 1:1 to prepare a mixed solution. The silicon carbide pretreated in step (1) is added to the above mixed solution, and then vinyltrimethoxysilane is added. The ratio of the amount of pretreated silicon carbide, vinyltrimethoxysilane and mixed solution is 3g:0.4g:400g. The reaction is stirred for 30min. The reaction solution is filtered and dried to obtain silicon carbide modified with silane coupling agent. (3) The silicon carbide modified with silane coupling agent obtained in step (1) and anhydrous ethanol are mixed evenly at a ratio of 1g:100mL. Then, trifluoroethyl methacrylate and azobisisobutyronitrile are added. The mass ratio of silicon carbide modified with silane coupling agent, trifluoroethyl methacrylate and azobisisobutyronitrile is 1:3:1.5. The mixture is reacted at 70℃ for 40min. Then, it is filtered, washed and dried to obtain modified silicon carbide fiber.
[0030] The preparation process of the nanofiller is as follows: Sodium hydroxide, urea, deionized water, and carboxymethyl cellulose are weighed according to a mass ratio of 7:12:100:4. Carboxymethyl cellulose is added to deionized water, followed by urea and sodium hydroxide. After stirring and mixing evenly, the mixture is freeze-dried to obtain pretreated carboxymethyl cellulose. Chitosan is dissolved in an 8% (w / w) acetic acid aqueous solution, with a mass ratio of chitosan to acetic acid aqueous solution of 1:10. The solution is heated to 60°C and stirred until dissolved to obtain an aqueous solution of chitosan. Nanographene is added to the chitosan aqueous solution. The mass ratio was 1:7, and the mixture was stirred at room temperature for 2 hours to obtain a dispersion. The dispersion was placed in a grinding bowl and continuously ball-milled at 400 rpm / min for 10 hours for exfoliation. The resulting product was dried under vacuum at 60℃. The dried product was added to deionized water, and then pretreated carboxymethyl cellulose was added. The ratio of the dried product, pretreated carboxymethyl cellulose, and deionized water was 5 g: 1.5 g: 100 mL. The mixture was reacted at 50℃ for 3 hours, allowed to stand for 12 hours, and then centrifuged at 5000 rpm for 30 minutes. The precipitate was washed with deionized water and dried to obtain the nanofiller.
[0031] This embodiment also provides a method for preparing a scratch-resistant coating, comprising the following steps: S1. Weigh each raw material according to the stated weight proportions, mix polyethylene glycol monomethyl ether acrylate, isodecanyl acrylate, and acrylic acid evenly, add 40% of the mass of the photoinitiator, and under nitrogen protection, use a 365nm ultraviolet lamp (intensity 20mW / cm²). 2 Under these conditions, the polymerization reaction yields acrylic resin; S2. Add reactive diluent, the remaining photoinitiator, and leveling agent to the acrylic resin, stir until homogeneous, then add nanofiller and stir until homogeneous; then add modified silicon carbide fiber and stir until homogeneous to obtain a coating. Apply the coating to the substrate surface and test under a 365nm ultraviolet lamp (intensity 20mW / cm²). 2 After curing, a scratch-resistant coating is obtained.
[0032] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that step (1) of the pretreatment process of silicon carbide fiber is omitted, while the rest is the same as Example 1.
[0033] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that step (3) is omitted in the preparation of modified silicon carbide fiber, while the rest is the same as Example 1.
[0034] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the nanofiller is replaced with nano-graphene, while the rest is the same as Example 1.
[0035] Performance testing (1) Scratch resistance: A five-finger scratch abrasion tester was used to perform a cross-cutting test with a force of 15N. Then, a colorimeter was used to test the brightness of the scratches and calculate the change in brightness (ΔL) before and after scratching.
[0036] (2) Abrasion resistance: Abrasion resistance was tested in accordance with GB / T 23988-2009 "Determination of Abrasion Resistance of Coatings by Falling Sand Method".
[0037] (3) Water contact angle: The water contact angle of the coatings obtained in Examples 1-3 and Comparative Examples 1-2 was measured using a contact angle measuring instrument.
[0038] (4) Adhesion: Tested according to GB / T9286-2021.
[0039] (5) Water resistance: GB / T1733-1993, immerse 2 / 3 of the coated sample in deionized water, soak for 240 hours, and observe whether the coating shows blistering, wrinkling, peeling or other phenomena.
[0040] (6) Salt spray resistance: The test shall be conducted in accordance with the test standard of GB / T10125-2021. The salt solution concentration shall be 50g / L and the test temperature shall be 35℃. After 1000h, observe whether the coating exhibits blistering, wrinkling, peeling or other phenomena.
[0041] Table 1 Observing the test results in Table 1, it can be seen that the products obtained in Examples 1-3 of this invention have good comprehensive properties such as scratch resistance, abrasion resistance, water resistance, and corrosion resistance. The smaller ΔL is, the stronger the scratch resistance of the material and the lighter the scratches. Compared with Example 1, Comparative Example 1 omits the pretreatment process of silicon carbide fiber in step (1), and the scratch resistance, abrasion resistance, and water contact angle of Comparative Example 1 are significantly reduced. This is because after omitting the pretreatment process of silicon carbide fiber, the reactivity of silicon carbide decreases and the bonding ability weakens, thus affecting the final effect of the coating. Compared with Example 1, Comparative Example 2 omits step (3) in the preparation of modified silicon carbide fiber, and the water contact angle is significantly reduced, resulting in a decrease in self-cleaning ability. Compared with Example 1, Comparative Example 3 replaces the nanofiller with nano-graphene, and the adhesion, water washing resistance, and salt spray corrosion resistance of the coating all show a downward trend. This shows that nanofillers play an important role in improving the comprehensive performance of coatings.
[0042] The above embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-substantial changes and substitutions made by those skilled in the art based on the present invention shall fall within the scope of protection claimed by the present invention.
Claims
1. A scratch-resistant coating, characterized in that, The coating comprises the following raw materials in parts by weight: 15-20 parts polyethylene glycol monomethyl ether acrylate, 25-30 parts isodecaacrylate, 40-50 parts acrylic acid, 10-15 parts reactive diluent, 4-5 parts photoinitiator, 0.5-1 part leveling agent, 3-7 parts nanofiller, and 8-12 parts modified silicon carbide fiber. The preparation process of the modified silicon carbide fiber is as follows: (1) Add silicon carbide fiber to the solvent, then add the catalyst, stir at room temperature, add tetrabutyl titanate, heat to react, separate the product, and heat the product to obtain pretreated silicon carbide. (2) Add the silicon carbide pretreated in step (1) to the solvent, then add the silane coupling agent, and after the reaction, obtain silicon carbide modified with silane coupling agent; (3) Add the silicon carbide modified by the silane coupling agent in step (1) to the solvent, then add methacrylate monomer and initiator, and after the reaction, obtain modified silicon carbide fiber.
2. The scratch-resistant coating according to claim 1, characterized in that, In step (1), the ratio of silicon carbide fiber, catalyst and tetrabutyl titanate is 1-2g: 1-1.5mL: 0.5-0.9mL; the ratio of silicon carbide fiber and solvent is 1-2g: 50mL; the catalyst is an ammonia solution with a mass concentration of 25%; and the solvent is anhydrous ethanol.
3. The scratch-resistant coating according to claim 1, characterized in that, In step (1), the stirring time at room temperature is 10-15 min; the heating reaction temperature is 40-50℃ and the time is 7-10 h; the heat treatment temperature is 270-280℃ and the time is 1-2 h.
4. The scratch-resistant coating according to claim 1, characterized in that, In step (2), the ratio of the amount of pretreated silicon carbide, silane coupling agent, and solvent is 3g:0.2-0.4g:300-400g; the solvent is prepared by mixing ethanol and water in a volume ratio of 1:1; the silane coupling agent is vinyltrimethoxysilane; and the reaction time is 20-30min.
5. The scratch-resistant coating according to claim 1, characterized in that, In step (3), the ratio of the amount of silicon carbide modified by the silane coupling agent to the solvent is 1g:60-100mL, and the mass ratio of the silicon carbide modified by the silane coupling agent, the methacrylate monomer, and the initiator is 1:(1.5-3):(1-1.5); the solvent is anhydrous ethanol; the methacrylate monomer is trifluoroethyl methacrylate; the initiator is azobisisobutyronitrile; the reaction temperature is 60-70℃, and the time is 40-60min.
6. The scratch-resistant coating according to claim 1, characterized in that, The preparation process of the nanofiller is as follows: Nanographene is added to an aqueous solution of chitosan and stirred at room temperature to obtain a dispersion. The dispersion is ball-milled and dried. The dried product is added to water, and then pretreated carboxymethyl cellulose is added. The mixture is heated to react and obtain the nanofiller.
7. The scratch-resistant coating according to claim 6, characterized in that, The preparation process of the pretreated carboxymethyl cellulose is as follows: Carboxymethyl cellulose is added to water, then urea and sodium hydroxide are added, stirred and mixed evenly, and then freeze-dried to obtain pretreated carboxymethyl cellulose; the mass ratio of sodium hydroxide, urea, water and carboxymethyl cellulose is (5-7):(8-12):(98-100):(3-4).
8. The scratch-resistant coating according to claim 6, characterized in that, The mass ratio of the nano-graphene and chitosan aqueous solution is 1:(5-7); the chitosan aqueous solution is prepared by mixing chitosan and acetic acid aqueous solution at a mass ratio of 1:(9-10), the concentration of the acetic acid aqueous solution is 5-8wt%, the stirring time at room temperature is 1-2h; the ball milling speed is 400-500rpm, and the time is 10-15h; the ratio of the dried product, pretreated carboxymethyl cellulose, and water is 5g:1-1.5g:90-100mL; the heating reaction temperature is 40-50℃, and the time is 3-5h.
9. The scratch-resistant coating according to claim 1, characterized in that, The reactive diluent is any one of 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, or trimethylolpropane triacrylate; the photoinitiator is 1-hydroxycyclohexylphenyl ketone; and the leveling agent is BYK-333.
10. The method for preparing the scratch-resistant coating according to any one of claims 1-9, characterized in that, Includes the following steps: S1. Weigh each raw material according to the stated weight parts, mix polyethylene glycol monomethyl ether acrylate, isodecanyl acrylate and acrylic acid evenly, add 30-40% of the mass of photoinitiator, and polymerize to obtain acrylic resin; S2. Add reactive diluent, the remaining photoinitiator, and leveling agent to acrylic resin and stir until homogeneous. Then add nanofiller and stir until homogeneous. Next, add modified silicon carbide fiber and stir until homogeneous to obtain a coating. Apply the coating to the surface of the substrate and cure it under ultraviolet light to obtain a scratch-resistant coating.
Citation Information
Cited By
Water-based coating for packaging material and preparation method of water-based coating
CN121873621A
Adhesive for repairing glass fiber reinforced plastic pipeline and preparation process thereof
CN121950226A
